I–V characteristics of graphene nanoribbon/h-BN heterojunctions and resonant tunneling. (6th June 2018) - Wakai, Taiga; Sakamoto, Shoichi; Tomiya, Mitsuyoshi
Abstract: We present the first principle calculations of the electrical properties of graphene sheet/h-BN heterojunction (GS/h-BN) and 11-armchair graphene nanoribbon/h-BN heterojunction (11-AGNR/h-BN), which are carried out using the density functional theory (DFT) method and the non-equilibrium Green's function (NEGF) technique. Since 11-AGNR belongs to the conductive (3n-1)-family of AGNR, both are metallic nanomaterials with two transverse arrays of h-BN, which is a wide-gap semi-conductor. The two h-BN arrays act as double barriers. The transmission functions (TF) and I – characteristics of GS/h-BN and 11-AGNR/h-BN are calculated by DFT and NEGF, and they show that quantum double barrier tunneling occurs. The TF becomes very spiky in both materials, and it leads to step-wise I – characteristics rather than negative resistance, which is the typical behavior of double barriers in semiconductors. The results of our first principle calculations are also compared with 1D Dirac equation model for the double barrier system. The model explains most of the peaks of the transmission functions nearby the Fermi energy quite well. They are due to quantum tunneling.